2006
DOI: 10.1063/1.2195879
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic force microscopy sensors using iron-filled carbon nanotubes

Abstract: Probes for magnetic force microscopy (MFM) were prepared by pinning iron-filled multiwall carbon nanotubes to conventional scanning force microscopy probes. These nanotube MFM probes reveal a great potential for high spatial resolution of both topography and magnetic stray field. The ends of the high aspect ratio iron nanowires within the nanotubes can be considered as stationary effective magnetic monopole moments which opens the possibility of quantitative stray field measurements in a straightforward manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(71 citation statements)
references
References 25 publications
0
70
0
1
Order By: Relevance
“…In order to improve the spatial resolution of the MFM technique, a further development of the magnetic probes is required. To achieve this goal, several approaches are described in the literature (Martin and Wickramasinghe, 1987;Göddenhenrich et al ., 1988Göddenhenrich et al ., , 1990Akama et al ., 1990;Rugar et al ., 1990;Vasile et al ., 1991;Grütter et al ., 1992;Wadas et al ., 1994;Moser et al ., 1995;Dai et al ., 1996;Jumpertz et al ., 1997;Hartmann, 1999;Wickramasinghe, 2000;Deng et al ., 2004;Winkler et al ., 2006) including three techniques that fulfil best the requirements of miniaturization: electron beam deposition (EBD) (Akama et al ., 1990;Jumpertz et al ., 1997), FIB milling (Vasile et al ., 1991) and attaching fullerene carbon multiwalled nanotubes (MWNTs) (Dai et al ., 1996) filled with magnetic material (Winkler et al ., 2006) or magnetically coated ones (Deng et al ., 2004) attached to microfabricated Si cantilever tips. The EBD and FIB approaches and the attached MWNTs proved to be the most successful ones, as the smallest sizes could be achieved: possible tip shanks could be as small as 5 nm in diameter.…”
Section: Introductionmentioning
confidence: 94%
“…In order to improve the spatial resolution of the MFM technique, a further development of the magnetic probes is required. To achieve this goal, several approaches are described in the literature (Martin and Wickramasinghe, 1987;Göddenhenrich et al ., 1988Göddenhenrich et al ., , 1990Akama et al ., 1990;Rugar et al ., 1990;Vasile et al ., 1991;Grütter et al ., 1992;Wadas et al ., 1994;Moser et al ., 1995;Dai et al ., 1996;Jumpertz et al ., 1997;Hartmann, 1999;Wickramasinghe, 2000;Deng et al ., 2004;Winkler et al ., 2006) including three techniques that fulfil best the requirements of miniaturization: electron beam deposition (EBD) (Akama et al ., 1990;Jumpertz et al ., 1997), FIB milling (Vasile et al ., 1991) and attaching fullerene carbon multiwalled nanotubes (MWNTs) (Dai et al ., 1996) filled with magnetic material (Winkler et al ., 2006) or magnetically coated ones (Deng et al ., 2004) attached to microfabricated Si cantilever tips. The EBD and FIB approaches and the attached MWNTs proved to be the most successful ones, as the smallest sizes could be achieved: possible tip shanks could be as small as 5 nm in diameter.…”
Section: Introductionmentioning
confidence: 94%
“…33 Also, aggregation of NWs has to be prevented in order to obtain high-quality homogeneous ferrofluids or to preserve the mechanical properties of composites containing magnetic NWs. 13 Magnetic dipolar interactions between magnetic particles dispersed in liquids are directly responsible for their agglomeration. In the absence of a magnetic field, such interactions are proportional to the overall remanent magnetization of each particle.…”
Section: Or Inmentioning
confidence: 99%
“…Many unique applications can be envisioned using these functional materials [60][61][62][63][64]. One example is the fabrication of nanothermometers consisting of liquid Ga filled CNTs, wherein our group showed that the liquid Ga column inside the CNT expands and compresses reversibly within a wide temperature range of about 500…”
Section: Properties and Prospects Of Filled Cntsmentioning
confidence: 99%